The Influence of Digital platforms, E-books, and Online publishing on the creation and dissemination of literature - SAIMA USMANI; ELSADIG HUSSEIN FADLALLA ALI; MUSADHIQUE KOTTAPARAMBAN (Research Journal in Advanced Humanities, 2025)
This study is significant for different stakeholders in the world of literacy and provides valuable insight for the author. It helps to understand the effect of modern technologies in shaping literature’s consumption, distribution, and reaction by informing marketing efforts and strategic decision-making.    The studies show how digital platforms, e-books, and online publishing have changed the dissemination and creation of literature in many ways, such as Accessibility, diverse publishing opportunities, interactivity and multimedia integration, global reach and culture exchange, data analytics, and personalization.